Impact of Deployment on Reproductive Health in U.S. Active-Duty Servicewomen and Veterans - Gawron, Lori M.; Mohanty, April F.; Kaiser, Jennifer E.; Gundlapalli, Adi V. (Seminars in Reproductive Medicine, 2018)
Reproductive-age women are a fast-growing component of active-duty military personnel who experience deployment and combat more frequently than previous service-era women Veterans. With the expansion of the number of women and their roles, the United States Departments of Defense and Veterans Affairs have prioritized development and integration of reproductive services into their health systems. Thus, understanding associations between deployments or combat exposures and short- or long-term adverse reproductive health outcomes is imperative for policy and programmatic development. Servicewomen and women Veterans may access reproductive services across civilian and military or Veteran systems and providers, increasing the need for awareness and communication regarding deployment experiences with a broad array of providers. An example is the high prevalence of military sexual trauma reported by women Veterans and the associated mental health diagnoses that may lead to a lifetime of high risk-coping behaviors that increase reproductive health risks, such as sexually transmitted infections, unintended pregnancies, and others. Care coordination models that integrate reproductive healthcare needs, especially during vulnerable times such as at the time of military separation and in the immediate postdeployment phase, may identify risk factors for early intervention with the potential to mitigate lifelong risks.
Keywords: women Veterans; reproductive health; deployment